INTERPRETATION AJIMAT KALIMASADA IN SERAT CENTHINI AS CULTURE ACCULTURATION - Yudi Pratama (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Ajimat Kalimasada (A story in Serat Centhini) classifiying historical periods and process of islamization in Java. Prior-assumption on Ajimat Kalimasada indicated the acculturation between Hindhuism ,Budhaism and Islamic cultures in the process of the islamization done by Sunan Kalijaga lied before the analysis contained in this paper. As for the approach, this study used Hermeneutical approach as one of a way to interprate the values contained in the story of Ajimat Kalimasada from historical perspective. The analitical result of Ajimat Kalimasada obviously depicted the methods used by Sunan Kalijaga in spreading the teaching of Islam in Java. The ability of Sunan Kalijaga in spreading Islam is manifasted in the story of Ajimat Kalimasada where there is a scene of a meeting between Sunan Kalijaga and Prabu Yudhistira and his moksa by saying syahada